CD43 signals induce Type One lineage commitment of human CD4+ T cells - Rosenstein Yvonne; Rosas-Salgado Gabriela; Esquivel-Guadarrama Fernando R; Cervantes-Badillo Mayte G; Rivera-Martínez Gemma M; Escobar-Zárate Diana L; Ramírez-Pliego Oscar; Santana M Angélica (BMC Immunology, 2007)
Abstract Background The activation and effector phenotype of T cells depend on the strength of the interaction of the TcR with its cognate antigen and additional signals provided by cytokines and by co-receptors. Lymphocytes sense both the presence of an antigen and also clues from antigen-presenting cells, which dictate the requisite response. CD43 is one of the most abundant molecules on the surface of T cells; it mediates its own signalling events and cooperates with those mediated by the T cell receptor in T cell priming. We have examined the role of CD43 signals on the effector phenotype of adult CD4+ and CD8+ human T cells, both alone and in the presence of signals from the TcR. Results CD43 signals direct the expression of IFNγ in human T cells. In freshly isolated CD4+ T cells, CD43 signals potentiated expression of the IFNγ gene induced by TcR activation; this was not seen in CD8+ T cells. In effector cells, CD43 signals alone induced the expression of the IFNγ gene in CD4+ T cells and to a lesser extent in CD8+ cells. The combined signals from CD43 and the TcR increased the transcription of the T-bet gene in CD4+ T cells and inhibited the transcription of the GATA-3 gene in both populations of T cells, thus predisposing CD4+ T cells to commitment to the T1 lineage. In support of this, CD43 signals induced a transient membrane expression of the high-affinity chains of the receptors for IL-12 and IFNγ in CD4+ T cells. CD43 and TcR signals also cooperated with those of IL-12 in the induction of IFNγ expression. Moreover, CD43 signals induced the co-clustering of IFNγR and the TcR and cooperated with TcR and IL-12 signals, triggering a co-capping of both receptors in CD4+ populations, a phenomenon that has been associated with a T1 commitment. Conclusion Our results suggest a key role for CD43 signals in the differentiation of human CD4+ T cells into a T1 pattern.